3.5(x+2.2y)+2(2.2x+1.7y)=

Simple and best practice solution for 3.5(x+2.2y)+2(2.2x+1.7y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3.5(x+2.2y)+2(2.2x+1.7y)= equation:


Simplifying
3.5(x + 2.2y) + 2(2.2x + 1.7y) = 0
(x * 3.5 + 2.2y * 3.5) + 2(2.2x + 1.7y) = 0
(3.5x + 7.7y) + 2(2.2x + 1.7y) = 0
3.5x + 7.7y + (2.2x * 2 + 1.7y * 2) = 0
3.5x + 7.7y + (4.4x + 3.4y) = 0

Reorder the terms:
3.5x + 4.4x + 7.7y + 3.4y = 0

Combine like terms: 3.5x + 4.4x = 7.9x
7.9x + 7.7y + 3.4y = 0

Combine like terms: 7.7y + 3.4y = 11.1y
7.9x + 11.1y = 0

Solving
7.9x + 11.1y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11.1y' to each side of the equation.
7.9x + 11.1y + -11.1y = 0 + -11.1y

Combine like terms: 11.1y + -11.1y = 0.0
7.9x + 0.0 = 0 + -11.1y
7.9x = 0 + -11.1y
Remove the zero:
7.9x = -11.1y

Divide each side by '7.9'.
x = -1.405063291y

Simplifying
x = -1.405063291y

See similar equations:

| (-9y-2z)(-8)= | | 1/16w^2+1/8w=1/2 | | 3d-4=d(d+8) | | 44x-4x=5x+18 | | -7-5x=5x+21 | | 10a+8b+4c-8d=7 | | 1-x=0.4 | | x^10=0.6 | | 6/7t=-48 | | 1-(x^10)=0.4 | | 5x-3=13-67 | | 2.8=14/x | | 2(r+5)=10-4r^2 | | 3t^3+5t=-8t^2 | | 2x^2y-5xy^2=0 | | (2x-3)(5x^2-2x+1)= | | z^2-20=22-z | | (-7x^3-2x-4)-(8x^2+4x-7)= | | 2x^2-6x+1=o | | 2p(p+4)=p^2+5p+10 | | 6y-8=40 | | 1/2+4/7p | | x+1.05x=20 | | -3(x+4)=24 | | 13c=2c^2+6 | | 64+x^3=0 | | -15-8b=9b+28 | | 0.5x-0.15=0.15 | | 10a^6/(2a^3) | | -6x+x^2+44.8*0.001=0 | | 0.24-2x=0.38 | | 6x+x^2+44.8*0.001=0 |

Equations solver categories